Reducing misdiagnosis of Alzheimer's Disease pathology utilizing CSF and amyloid PET. (20th December 2022) - Esquivel, Rianne N; De Simone, Francesca; Benina, Natalya; Gannon, Sara; Bastard, Nathalie Le; Calabro, Amanda; Hawkins, Douglas M; Vandijck, Manu; Latham, Jessica; Dickson, Diana; Radwan, Rachel R.
Abstract: Background: Utilizing cognitive tests alone, including the Mini‐Mental State Examination (MMSE) or the Montreal Cognitive Assessment (MoCA), cannot detect the presence of amyloid plaques and tangles in Alzheimer's disease (AD). While in late stages of AD clinical diagnosis relying primarily on cognitive testing is correct 70‐90% of the time, in MCI accuracy is reduced to 50‐60%. Although autopsy is the gold standard for AD diagnosis, amyloid PET imaging and more recently the Lumipulse G β‐Amyloid Ratio (Aβ1‐42/Aβ1‐40) are validated to determine amyloid pathology. With the upcoming availability of disease modifying therapies targeting amyloid in MCI and early AD, and anti‐tau drugs in the pipeline, it is necessary to have true measures of AD pathology for a clinical evaluation early in the disease process. Here we examine the performance of cognitive testing alone for identification of amyloid positivity in MCI patients from the ADNI study when compared to amyloid PET and CSF testing. Method: A subset of 170 CSF samples from the ADNI biobank (all MCI; ≥ 50 years old; amyloid PET negative (n=74) or amyloid PET positive (n=96)) was used to examine correlation of PET, CSF and MMSE/MoCA scores. Amyloid PET images were derived from an FDA approved tracer (Florbetapir F18) and method. CSF Aβ1‐42 and Aβ1‐40 were measured using the LUMIPULSE G1200 (Fujirebio). Result: At a set cutoff of 0.058, Aβ1‐42/Aβ1‐40 demonstrated a PPA and NPA of 85.9% and 93.5% respectively for identifying amyloid PET status in individuals suffering from cognitive complaints. When examining the Aβ1‐42/Aβ1‐40 ratio of the MCI patients compared to amyloid PET in ADNI, Aβ1‐42/Aβ1‐40 achieved an AUC of 0.90. Alternatively, the MMSE score and MOCA score had AUCs with amyloid PET of 0.61 and 0.63 respectively and exhibited poor correlation with CSF. Conclusion: CSF measurements or amyloid PET provide greater accuracy in determining amyloid status than cognitive screening tests. MMSE or MoCA as standalone tests give low confidence in a correct pathological diagnosis for MCI patients. Moving forward it will be important to consider PET or CSF results to determine underlying pathology in patients with MCI to ensure proper treatments and avoid unwanted side effects.